FENOMENA PEMBIAYAAN BAGI HASILPADA BMT UGT NUSANTARA DI PASURUAN - Soleh, Badrus; Ridwan, Muhtadi; Khusnudin, Khusnudin (ITB AAS Indonesia Surakarta, 2024)
This research aims to analyze the obstacles that are factors in the lack of profit sharing financing at BMT UGT Nusantara. This research uses a qualitative approach with phenomenological methods to examine the process of determining financing schemes, implementing profit sharing financing and identifying the causes of the lack of profit sharing financing at BMT UGT Nusantara. Data collection was carried out through in-depth interviews with informants such as financial managers, business managers, branch heads, account officers and members of BMT UGT Nusantara. Apart from that, field observations and analysis of financing documents were also carried out to obtain a comprehensive picture. Data analysis was carried out using three analytical steps suggested by Miles and Huberman (2007), namely data reduction, data exposure and conclusion drawing or verification. The results of this research indicate that determining the financing scheme is the internal authority of BMT UGT Nusantara with the knowledge and approval of members. Financing with a profit sharing scheme is only used for companies that are already established, while small businesses use non-profit sharing financing. The lack of financing with a profit sharing scheme is due to several obstacles such as high risk, quality of human resources, asymmetric information, moral hazard, minimal understanding of members and member preferences.